The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1158/1940-6207.capr-15-0402
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene 9′,10′ Oxygenase Modulates the Anticancer Activity of Dietary Tomato or Lycopene on Prostate Carcinogenesis in the TRAMP Model

Abstract: The hypothesis that dietary tomato consumption or the intake of the carotenoid lycopene inhibits prostate cancer arose from epidemiologic studies and is supported by preclinical rodent experiments and in vitro mechanistic studies. We hypothesize that variation in activity of carotenoid cleavage enzymes, such as β-carotene 9’,10’-oxygenase (BCO2), may alter the impact of dietary tomato and lycopene on prostate carcinogenesis and therefore examined this relationship in the TRAMP model. Starting at three weeks of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 60 publications
2
32
0
1
Order By: Relevance
“…As polar extracts of the plasma were analyzed, non‐polar carotenoids were not present in these extracts. We have previously reported blood concentrations of lycopene (25 μM) in mice fed the same red tomato‐ and lycopene‐containing diets …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As polar extracts of the plasma were analyzed, non‐polar carotenoids were not present in these extracts. We have previously reported blood concentrations of lycopene (25 μM) in mice fed the same red tomato‐ and lycopene‐containing diets …”
Section: Resultsmentioning
confidence: 99%
“…The tomato and control diets contained placebo beadlets (0.25 %) to match the other components of the lycopene beadlets. The red tomato diet and lycopene diet were formulated to deliver the same amount of lycopene and have demonstrated biological activity in mice . Diets were stored in the dark at ‐20°C to minimize the degradation and oxidation of phytochemicals over the course of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from studies in transgenic mouse models of prostate cancer that metabolites similar to bixin are the molecular species responsible for the cancer preventive effects of lycopene. 138 Bixin has an excellent safety record and good systemic bioavailability when orally administered. A team from the Arizona Cancer Center recently reported that intraperitoneal injection of bixin activates the transcription factor Nrf2 and thereby induces an antioxidant response in a mouse model of UVinduced photodamage and inflammation.…”
Section: Lycopene and Related Carotenoidsmentioning
confidence: 99%
“…It is used worldwide as a dietary additive and cosmetic ingredient known as annatto. There is evidence from studies in transgenic mouse models of prostate cancer that metabolites similar to bixin are the molecular species responsible for the cancer preventive effects of lycopene 137 . Bixin has an excellent safety record and good systemic bioavailability when administered orally.…”
Section: Introductionmentioning
confidence: 99%